2022
DOI: 10.1186/s12913-022-07961-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life (QoL) among COVID-19 recovered healthcare workers in Bangladesh

Abstract: Background The Coronavirus Disease 2019 (COVID-19) caused by the SARS-CoV-2 virus has taken the lives of more than 100,000 healthcare workers (HCWs) so far. Those who survived continuously work under immense physical and psychological pressure, and their quality of life (QoL) is impacted. The study aimed to assess the QoL among HCWs in Bangladesh who recovered from COVID-19. Methods This cross-sectional, telephonic interview-based study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
2
17
0
1
Order By: Relevance
“…Similar results are also found in some studies conducted in the UK and Wuhan in China (Halpin et al, 2021;Huang et al, 2021). Meanwhile, our respondents also mentioned that they also faced various social and economic crisis in their post-COVID-19 days which is also consistent with some other studies across the world (Missel et al, 2022;Rashid et al, 2022;Uddin et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results are also found in some studies conducted in the UK and Wuhan in China (Halpin et al, 2021;Huang et al, 2021). Meanwhile, our respondents also mentioned that they also faced various social and economic crisis in their post-COVID-19 days which is also consistent with some other studies across the world (Missel et al, 2022;Rashid et al, 2022;Uddin et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…stigma in healthcare settings and outside (Farhana, 2020;Akhter et al, 2021;Khan Rony et al, 2021;Khatun et al, 2021;Rana and Islam, 2021;Razu et al, 2021;Sakib et al, 2021;Mehedi and Ismail Hossain, 2022;Miah et al, 2022;Pooja et al, 2022;Rahman, 2022;Tune et al, 2022;Uddin et al, 2022). In addition, a group of researchers in Bangladesh conducted a telephonebased survey of 322 healthcare professionals to examine their quality of life after being cured of coronavirus (Rashid et al, 2022). Moreover, prior COVID-19 research did not examine the lived experiences of various infected frontline workers, including healthcare providers, law enforcement personnel, journalists, and bankers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Also, in Italian study, participants reporting PTSD with comorbid depression had higher each domain scores. (12) Finally, Regarding to our comparison of four domains across place of work which recently discussed in our study, the physical health domain was higher in governmental workplace than in military workplace. Furthermore, the psychological domain was higher in governmental workplace than in private workplace and in military workplace than in private workplace.…”
Section: Discussionmentioning
confidence: 56%
“…In a study of Suryavanshi et al, moderate and severe anxiety and depression were significantly associated with QoL among 197 healthcare professionals [ 19 ]. In addition to studies reported in the review, there were two studies assessing risk factors for QoL among HCWs [ 27 , 28 ]. Rashid et al reported socio-demographic risk factors associated with QoL among 322 HCWs from Bangladesh [ 28 ].…”
Section: Introductionmentioning
confidence: 99%